Shortages, high-demand occupations, and the post-Brexit UK immigration system - Sumption, M (Oxford University Press, 2022)
One of the key questions facing immigration policy-makers is which jobs should be eligible for work visas. This question has dominated discussions about the post-Brexit immigration system, which has focused in particular on the issue of shortages. While the UK government resisted calls to open labour migration routes in low-wage or low-skilled jobs with high demand for foreign workers, workers in middle- and high-skilled jobs that are deemed to face a labour market shortage can qualify with significantly lower wages. This paper examines the arguments for and against using immigration policy to prioritize labour migration in ‘shortage occupations’. It argues that the idea is politically appealing but problematic in practice. Shortages are more difficult to measure satisfactorily than policy-makers may imagine, and different methodologies produce different results. This makes it unwise to develop an immigration policy that depends too heavily on the notion that the shortage list is an accurate reflection of what is really happening in the labour market.